STRATEGI PENGEMBANGAN TERNAK SAPI POTONG BERWAWASAN AGRIBISNIS DI PROVINSI ACEH - Hendra Saputra; Arief Daryanto; Dudi S. Hendrawan (Jurnal Manajemen & Agribisnis, 2009)
The main objectives of this research are to analyze the development strategy of livestock implemented in the Province of Aceh, identify and analyze the factors that are involved, which from a determinant of beef cattle development through agribusiness insight. Furthermore, this research was aimed to arrange alternative strategy, and recommend its priority to the Animal Husbandry of Aceh Province. The research method used was descriptive method by means of survey research, and the sampling technique used was non-probability technique through purposive sampling. The analysis tool used were Internal Factor Evaluation (IFE) analysis, External Factor Evaluation (EFE) analysis, SWOT analysis, and QSPM analysis. Determining of strategy priority that done by QSPM analyze, obtained the strategy that has the main priority that can be implemented  in development of beef cattle agribusiness conception; development  of beef cattle bussiness through the implementation of integrated farming area (cluster) that in supported by subsystems availability in agribusiness of beef cattle from the upstream subsytem to downstream subsystem and support services.